Bridging technology and care: integrating web-based PROMs in mental health services for refugees: a study on clinician training and technology adoption - Moeller, Stine Bjerrum; Kring, Lotte (Frontiers in Psychology, 2024)
This study explores the integration of a web-based electronic database technology containing patient-reported outcome measures (PROMs) with electronic health records for refugees with PTSD, emphasizing the systematic inclusion of patient perspectives in clinical decision-making. Our research addresses the notable gap in literature regarding training clinicians for the competent integration of health information technology in healthcare. The training program developed aimed at equipping clinicians, particularly inexperienced with technology, to effectively utilize an electronic PROM system for collecting systematic patient information. Our study is set in the context of the Mental Health Services (MHS) in Denmark, focusing on a specialized clinic for treating trauma-affected refugees. The multidisciplinary team involved in this project reflects a wide range of healthcare professionals. The training program employed a variety of activities over nearly two years, adapting to feedback and aiming to engage clinicians in continuous improvement processes. Analyzing qualitative data with thematic analysis we interpreted that the training's extended focus on discussion of the implementation process, with limited hands-on experience, potentially reinforced clinicians' hesitations towards new technology, rather than reducing them. Clinicians prioritized immediate concerns over potential long-term benefits. Despite this, their approach reflects a strong commitment to patient welfare and careful evaluation of new practices. Notably, there were also positive engagements with the technology, highlighting its potential in patient care. This study concludes that the successful integration of technology in clinical settings hinges on its alignment with clinicians' workflows, respect for their professional judgment, and clear benefits to patient care.